2008
DOI: 10.1007/s00702-008-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Early cortical processing of natural and artificial emotional faces differs between lower and higher socially anxious persons

Abstract: Emotional facial expressions provide critical information for social interactions. Above all, angry faces are assumed to reflect potential social threat. We investigated event-related potentials (ERPs) triggered by natural and artificial faces expressing fear, anger, happiness or no emotion in participants with low and high levels of social anxiety. Overall, artificial faces elicited stronger P100 and N170 responses than natural faces. Additionally, the N170 component was larger for emotional compared to neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
148
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(185 citation statements)
references
References 69 publications
33
148
4
Order By: Relevance
“…Based on these previous ERP results (Vuilleumier & Pourtois, 2007), we surmised that the N170 would be larger for neutral faces used as negative feedback, compared to positive feedback. By contrast, since previous ERP studies mainly failed to provide evidence for a clear effect of anxiety at this early stage of face processing (Kolassa et al, 2007;Kolassa & Miltner, 2006;Muhlberger et al, 2009;Rossignol et al, 2005), we did not predict any strong effect of trait anxiety on the amplitude of the N170.…”
contrasting
confidence: 99%
“…Based on these previous ERP results (Vuilleumier & Pourtois, 2007), we surmised that the N170 would be larger for neutral faces used as negative feedback, compared to positive feedback. By contrast, since previous ERP studies mainly failed to provide evidence for a clear effect of anxiety at this early stage of face processing (Kolassa et al, 2007;Kolassa & Miltner, 2006;Muhlberger et al, 2009;Rossignol et al, 2005), we did not predict any strong effect of trait anxiety on the amplitude of the N170.…”
contrasting
confidence: 99%
“…Many studies asked for simple ratings of valence and/or arousal (Amir et al, 2005;Amir et al, 2010;Evans et al, 2008;Heuer et al, 2007;Merckelbach et al, 1989;Mühlberger et al, 2009;Straube et al, 2004;Wieser et al, 2011;Wieser et al, 2009). From a psychopathological perspective, these judgments may not necessarily tap into the phenomenology of social anxiety.…”
Section: Discussion and Integration Of Results To Datementioning
confidence: 99%
“…For example, some authors implemented the self-ratings as an addition to a functional magnetic resonance imaging (fMRI) task (Evans et al, 2008;Stein et al, 2002;Straube et al, 2004;Straube et al, 2005) or to a study collecting electromyogram (EMG) or electroencephalogram (EEG) data (Dimberg & Thunberg, 2007;Mühlberger et al, 2009;Wieser et al, 2011). Upon completing the physiological recordings, the same stimuli used in the main task were then presented to the participants again to gather reports of perceived valence.…”
Section: Discussion and Integration Of Results To Datementioning
confidence: 99%
See 1 more Smart Citation
“…ERPs can provide a temporally precise, direct measure of covert attention and may detect biases not evident in behavioral data (see Kappenman, Farrens, Luck, & Proudfit, 2014). Several studies using ERPs and related approaches have suggested that socially anxious individuals display enhanced attention to emotional faces (McTeague, Shumen, Wieser, Lang, & Keil, 2011;Rossignol, Campanella, et al, 2012;Rossignol, Philippot, Bissot, Rigoulot, & Campanella, 2012), especially those which are aversive (Kolassa, Kolassa, Musial, & Miltner, 2007;Moser, Huppert, Duval, & Simons, 2008;Mueller et al, 2009;Mühlberger et al, 2009;Sewell, Palermo, Atkinson, & McArthur, 2008). For example, studies have found evidence of enhanced attention for angry faces in social anxiety as indicated by the P2 (Rossignol, Campanella, Bissot, & Philippot, 2013;Van Peer, Spinhoven, & Roelofs, 2010), although other studies suggest enhanced attention for faces more generally (Rossignol, Philippot, Bissot, Rigoulot, & Campanella, 2012) or not at all (Kolassa et al, 2009).…”
mentioning
confidence: 99%